2013
DOI: 10.1177/0300060513480920
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of DEPTOR inhibits cell proliferation and increases chemosensitivity to melphalan in human multiple myeloma RPMI-8226 cells via inhibiting PI3K/AKT activity

Abstract: Objective: The present study determined the role of DEP domain containing mTOR-interacting protein (DEPTOR) in the proliferation, apoptosis and chemosensitivity of RPMI-8226 multiple myeloma cells, using small hairpin RNA (shRNA) to knock down DEPTOR gene expression in vitro. Methods: DEPTOR mRNA and protein levels in RPMI-8226 cells treated with DEPTOR-specific shRNA were evaluated by reverse transcription-polymerase chain reaction and Western blotting. Expression of apoptosis-associated proteins (including c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…Our study also revealed that expression of P-S6 (S235/236) was significantly higher in CRC tissue than in normal colorectal mucosa (p<0.01). When greatly overexpressed, DEPTOR inhibits mTORC1 (Peterson et al, 2009;Bruneau et al, 2013;Meng et al, 2013;Zhang et al, 2013). In this study, DEPTOR was equally expressed in CRC and adjacent DOI:http://dx.doi.org/10.7314/APJCP.2014.15.11.4589 DEPTOR Expression Negatively Correlates with mTORC1 Activity and Tumor Progression in Colorectal Cancer normal colorectal mucosa.…”
Section: Discussionmentioning
confidence: 56%
“…Our study also revealed that expression of P-S6 (S235/236) was significantly higher in CRC tissue than in normal colorectal mucosa (p<0.01). When greatly overexpressed, DEPTOR inhibits mTORC1 (Peterson et al, 2009;Bruneau et al, 2013;Meng et al, 2013;Zhang et al, 2013). In this study, DEPTOR was equally expressed in CRC and adjacent DOI:http://dx.doi.org/10.7314/APJCP.2014.15.11.4589 DEPTOR Expression Negatively Correlates with mTORC1 Activity and Tumor Progression in Colorectal Cancer normal colorectal mucosa.…”
Section: Discussionmentioning
confidence: 56%
“…DEPTOR interacts with mTOR and inhibits mTORC1/2 pathways (Peterson et al, 2009). It plays an important role in proliferation (Zhang et al, 2013b), apoptosis (Zhang et al, 2013a), regulation pluripotency of embryonic stem cells (Agrawal et al, 2014), and adipogenesis . Recent studies reveal that DEPTOR is a critical upstream regulator of vascular endothelial cells (ECs) activation and is involved in the inflammatory response of ECs (Bruneau et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Because MM cell lines generally grow in suspension or at best semi-adherently, they belong among the harder-to-manipulate cell types by transient transfection methodologies. Even though a number of papers either deal with this issue or report MM cell transfection in their methods chapter [14], [15], [16], [17], [18], [19], [20], a robustly workable and widely-used protocol has not yet emerged. Our analyses of MM cell electroporability with siRNAs were therefore not only intended to address the purely functional aspects, but also to judge whether such a protocol could i) easily be performed and replicated by other researchers in their laboratories, ii) prove cost-effective, and iii) could be applied to generate sufficient numbers of transfected cells to conduct experiments that require substantial amounts of material, such as, for example, nuclear preparations (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Growing in suspension and/or semi-adherently, HMCLs do not count as particularly amenable to transient transfection with nucleic acids. Few publications have specifically addressed this topic [12], [13] and although a roster of anecdotal evidence implies various transient transfection methodologies for use with (specific) HMCLs [14], [15], [16], [17], [18], [19], [20], no broadly-used method of choice has so far emerged – not least, because transfection efficiency is usually either perceived as low or not easily determined in the first place. RNAi knockdown experiments in HMCLs can usefully complement pharmacologic inhibition studies and also offer a chance to target undruggable proteins.…”
Section: Introductionmentioning
confidence: 99%